Country CSA profiles developed by CCAFS to guide CSA mainstreaming into the National Agricultural Investment Plans of West African Countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
In the framework of the climate-smart agriculture (CSA) prioritization framework developed by CCAFS and in view of the evidence of the CSA profile developed by CCAFS for Senegal, the Food and Agriculture Organization of the United Nations (FAO) contracted CCAFS WA to develop CSA profiles for the Gambia, Benin, Niger and Côte d’Ivoire. FAO has confirmed to CCAFS that the CSA profiles will guide the recommendations for CSA mainstreaming into the national agricultural investment plans of selected West African countries.